A novel energy poverty evaluation: Study of the European Union countries. (1st February 2023) - Hasheminasab, Hamidreza; Streimikiene, Dalia; Pishahang, Mohammad
Abstract: Energy plays a pivotal role in economic growth. Besides, it is a requirement for the factories to be run, Industries to be developed, cities to have functioned, and populations to fulfill their needs and expectations. Thus, energy has a strategic position among nations and countries. Align with sustainability, nations want to have energy justice among various generations. In this regard, this study developed a comprehensive framework based on a complete literature review, to evaluate energy poverty (EP) by addressing the energy demand, clean generation of the energy, its strategic position, and energy justice among the nations. As a consequence, the EP framework consists of three pillars. The first one is for society to address the demand, access, and affordability of energy. The second pillar is administration to ensure the accessibility to the sources of energy as well as aligning the energy market by their import policies. The third EP pillar is sustainability and refers to the emissions which result from the energy generations and level of renewable energy sources to satisfy the energy demand. By considering these three pillars, energy would be accessible, affordable, and sustained among various generations. The comprehensive EP framework is applied in a case study with real data by using the European Union (EU) energy goal (7th goal) among the sustainable development indicators. The EP comprehensive framework is implemented to evaluate 27 EU countries based on the EU database in this case study by using the Indifference Threshold-based Attribute Ratio Analysis (ITARA) to weigh up the criteria set since this method is the recommended method in case of dealing with real data and assist the study to accurate and independent to the expert background and their attitude. Also, Measurement Alternatives and Ranking according to COmpromise Solution (MARCOS) methodology is used to evaluate the EU countries as the methodology uses both positive and negative ideal solutions to make sure the accuracy and convergence speed particularly when the problem is confronted by a long list of the 27 EU countries. Highlights: A novel a comprehensive framework to assess energy poverty. Accessibility, affordability and sustainability criteria. Indifference Threshold-based Attribute Ratio Analysis. COmpromise Solution (MARCOS) methodology. Applied for 27 EU Member States in 2015–2020.